The properties of large coal particles and reaction kinetics of corresponding chars. (15th January 2015) - Everson, R.C.; Neomagus, H.W.J.P.; van der Merwe, G.W.; Koekemoer, A.; Bunt, J.R.
Highlights: The chemical, petrographic and physical properties of coal particles of different sizes and densities were determined. The distribution of properties depended on the densities of the particles. The combustion reaction rates for large particles and for different particles sizes and densities were measured. The combustion rates were characterised with a shrinking core with diffusion controlled mechanisms only. Abstract: An investigation was undertaken to determine the distribution of chemical-, petrographic- and mineralogical properties of large coal particles of different sizes and densities and to evaluate a suitable reaction rate model for combustion of corresponding chars. This was undertaken in order to contribute to the knowledge of the combustion kinetics of large particles in fluidized bed combustion and moving bed combustion/gasification. The study was confined to a mineral rich (24.1 wt%) and inertinite rich (74 wt%) parent coal (precursor) that was separated into different sizes and density fractions. The combustion reactive properties of chars prepared at 1100 °C and at a reaction temperature of 1000 °C were determined using a horizontal tubular furnace with the associated on-line analysers and temperature controllers. Coal particles in the size range of 0.50–53 mm diameter and density from 1.4 g cm −3 to 2.0 g cm −3 were studied. The characterisation of the different coal samples consisting of ash content, maceral content, fuel ratios and calorific values showed that the parameters did not vary significantly over the particle size ranges, but were different for the different density fractions. Combustion studies showed that particle size and density influenced the time required for complete conversion of the chars. The smaller particles and low density particles reacted faster and the modeling of the experimental data showed that the isothermal shrinking un-reacted core model with film and ash layer diffusion was applicable. The effective ash layer diffusion becomes more prominent as the density increased and the mass transfer coefficients correlated well with published results.